2022
DOI: 10.1186/s12967-022-03296-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota medicine: towards clinical revolution

Abstract: The human gastrointestinal tract is inhabited by the largest microbial community within the human body consisting of trillions of microbes called gut microbiota. The normal flora is the site of many physiological functions such as enhancing the host immunity, participating in the nutrient absorption and protecting the body against pathogenic microorganisms. Numerous investigations showed a bidirectional interplay between gut microbiota and many organs within the human body such as the intestines, the lungs, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(105 citation statements)
references
References 255 publications
(248 reference statements)
0
101
0
4
Order By: Relevance
“…The interactions between the GM and extraintestinal organs have been grouped and are referred to as interorganic axes [ 16 ]. It is now well established that the GM plays an essential role in the development or alleviation of diseases in these specific organs outside the intestinal tract by providing an alternative means of worsening inflammation or improving symptoms.…”
Section: Intestinal Microbiota and Dysbiosismentioning
confidence: 99%
See 1 more Smart Citation
“…The interactions between the GM and extraintestinal organs have been grouped and are referred to as interorganic axes [ 16 ]. It is now well established that the GM plays an essential role in the development or alleviation of diseases in these specific organs outside the intestinal tract by providing an alternative means of worsening inflammation or improving symptoms.…”
Section: Intestinal Microbiota and Dysbiosismentioning
confidence: 99%
“…It has even been observed that a communication system exists between gut bacteria and the CNS. These findings have led to the description of the “microbiota–gut–brain axis.” This axis includes connections between different biological systems to regulate homeostatic processes at the GI level, in the CNS, and in the gut bacteria themselves [ 16 , 28 ].…”
Section: Microbiota–gut–brain Axis (Mgb)mentioning
confidence: 99%
“…The vast majority correspond to bacteria belonging to Phyla Firmicutes, Bacteroidetes, Actinobacteria, Proteobacteria, Fusobacteria and Verrucomicrobia, and the existence of 150 times more genes than in the human genome has been demonstrated ( 22 , 23 ). It consists of more than 100 trillion microbial cells that interfere not only in intestinal and absorptive functions, but also in a wide network of neuronal, mental, immunological, endocrine, and metabolic actions ( 24 ).…”
Section: Gut Microbiota Aging and Alzheimer's Diseasementioning
confidence: 99%
“…For example, in the gastrointestinal system, the microbiome helps in the absorption of nutrients. They protect against pathologic bacteria and play a key role in the regulation of the host immune system [ 7 ]. This intricate relationship can sometimes lead to disease development, especially when there are changes in homeostasis.…”
Section: Introductionmentioning
confidence: 99%